Analisis harga dan kualitas produk serta pengaruhnya terhadap loyalitas konsumen pada Rijan Mart I Prambon Sidoarjo - Imam Wahyudi (FADZAT: Jurnal Ekonomi Syariah, 2022)
The purpose of this study was to analyze the simultaneous, partial and dominant effect of the variable price and product quality on consumer loyalty. The research method explains that the location as a business institution, the type of research is explanatory research, namely research that aims to determine the relationship between the two variables price and product quality on consumer loyalty. The research population is consumers who are taken incidentally. Data analysis used multiple linear regression. The results showed that: 1) price and product quality had a simultaneous effect on consumer loyalty. 2) price and product quality have a partial effect on consumer loyalty. 3) product quality has a dominant effect on consumer loyalty.